A CONTRIBUTION TO THE RESEARCH OF MOSTAR MILJEVINA WITH SPECIAL REFERENCE TO FROST RESISTANCE - Milica Rončević; Krešimir Šaravanja; Tomislav Marić; Jelena Radić Kustura (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta)
The paper presents the freshwater limestone Mostar miljevina (miljevina). In the diagenesis process, it acquired a specific orientation and structure, which gave it specific physical properties that geologically older, compact (dense) limestones do not have. The results of the previous tests of miljevina from the Mukoša deposit near Mostar and from several buildings in Mostar are presented. Miljevina is less crystalline, less dense, and thereby less resistant to the processes of chemical deterioration and deterioration caused by crystallization. Due to the high absolute porosity of the open pores, miljevina has high moisture absorption and pronounced capillary water absorption, so it was not desirable to install it on surfaces directly exposed to wetting by rain and gusts of wind, but it was protected by facades, with the use of another type of stone in the part of the building in contact with the ground.The second part of the paper presents the results of testing miljevina as part of the graduation thesis, especially frost resistance, with appropriate conclusions and comparisons with previous results.